Extracorporeal CO2 removal as bridge to lung transplantation in life‐threatening hypercapnia. (5th December 2014) - Schellongowski, Peter; Riss, Katharina; Staudinger, Thomas; Ullrich, Roman; Krenn, Claus G.; Sitzwohl, Christian; Bojic, Andja; Wohlfarth, Philipp; Sperr, Wolfgang R.; Rabitsch, Werner; Aigner, Clemens; Taghavi, Shahrokh; et al.
Summary In patients awaiting lung transplantation (LTX), adequate gas exchange may not be sufficiently achieved by mechanical ventilation alone if acute respiratory decompensation arises. We report on 20 patients with life‐threatening hypercapnia who received extracorporeal CO2 removal (ECCO2‐R) by means of the interventional lung assist (ILA®, Novalung) as bridge to LTX. The most common underlying diagnoses were bronchiolitis obliterans syndrome, cystic fibrosis, and idiopathic pulmonary fibrosis, respectively. The type of ILA was pumpless arteriovenous or pump‐driven venovenous (ILA activve®, Novalung) in 10 patients each. ILA bridging was initiated in 15 invasively ventilated and five noninvasively ventilated patients, of whom one had to be intubated prior to LTX. Hypercapnia and acidosis were effectively corrected in all patients within the first 12 h of ILA therapy: PaCO2 declined from 109 (70–146) to 57 (45–64) mmHg, P < 0.0001; pH increased from 7.20 (7.06–7.28) to 7.39 (7.35–7.49), P < 0.0001. Four patients were switched to extracorporeal membrane oxygenation due to progressive hypoxia or circulatory failure. Nineteen patients (95%) were successfully transplanted. Hospital and 1‐year survival was 75 and 72%, respectively. Bridging to LTX with ECCO2‐R delivered by arteriovenous pumpless or venovenous pump‐driven ILA is feasible and associated with high transplantation and survival rates.